Child Sexual Abuse as Lifespan Trauma Within the Context of Intimate Partner Violence: Experiences of Caribbean Women - Jones, Adele D. (Frontiers in Sociology, 2021)
Background: There is a dearth of research which explores sexual abuse from perspectives of Caribbean women, despite its high prevalence in the region. While sexual violence is universal, tackling it requires a deep understanding of the contextual specificities in which it arises and of the intersections of gender with other sources of oppression and marginalization. It also calls for the recognition that intimate partner violence against women is not separate from, but linked to violence against girls, not only because both are forms of gender-based violence but because together they speak to its historical, persistent and accumulative effects. Methods: In-depth intensive interviews were carried out with 35 women from Barbados and Grenada, aged 18-60 years who had experienced intimate partner violence under one of the following circumstances: during pregnancy (n=15), as a woman a with disability (n=8), as a woman living with HIV (n=12). Interviews were digitally recorded, transcribed and thematically analyzed. Results: The participants experienced multiple forms of violence within their relationships, often concurrently. Twenty-one of the women had been subject to sexual violence and of these, 19 had experienced sexual abuse as children; these experiences were viewed as interconnected and bolstered by the high level of violence-acceptance reported within communities. Women were subject to different forms of control by their partners depending upon prevailing discourses related to their circumstances (as pregnant, disabled, or HIV positive); being ‘vulnerable’ was synonymous with having one’s agency as an independent, autonomous person constrained and little external help was available. Conclusion: The study identified a clear chain of sexual behaviors, each of which fuel different layers of the problem: the prevalence of early sexualization of children is associated with the prevalence of child sexual abuse; child sexual abuse is pervasive in large part, because of the normalization and social acceptance of violence against women and girls; ‘cultural’ normalcy, in turn, fuels attitudes which contribute to sexual violence against women and women in especially vulnerable circumstances face additional risks. Integrated policy, which tackles these as interconnected issues is called for.